Cascade trifluoromethylthiolation and cyclization of N-[(3-aryl)propioloyl]indoles - Bi, Ming-Xi; Liu, Shuai; Huang, Yangen; Xu, Xiu-Hua; Qing, Feng-Ling (Beilstein Journal of Organic Chemistry, 2020)
A cascade oxidative trifluoromethylthiolation and cyclization of N-[(3-aryl)propioloyl]indoles with AgSCF3 is described. This protocol allows for the synthesis of novel bis(trifluoromethylthiolated) or trifluoromethylthiolated pyrrolo[1,2-a]indol-3-ones in moderate to good yields. Mechanistic investigations indicated that radical processes were probably involved in these transformations.
Keywords: cyclization; indole derivatives; oxidation; radical reaction; trifluoromethylthiolation